Comparison of tragal perichondrium and COOK artificial material in endoscopic type 1 tympanoplasty - Gaofei Ye; Mingguang Zhou; Wenya Li; Xiuwen Jiang (Laparoscopic, Endoscopic and Robotic Surgery, 2023)
Objective: Various materials have been used for tympanic membrane reconstruction in middle ear surgery. This study aimed to evaluate the difference between the tragal perichondrium and COOK artificial material in patients who underwent endoscopic type 1 tympanoplasty. Method: This retrospective study included patients who underwent endoscopic type 1 tympanoplasty from June 2021 to June 2022 at Sir Run Run Shaw Hospital, Zhejiang University School of Medicine. Patients were divided into group A (tragal perichondrium) and group B (COOK artificial material) according to the material used in the operation. All patients were followed up for 6 months. The differences in age, gender, operation site, disease course, preoperative air-bone gap (ABG), operation time, blood loss, hearing gain, and wound healing rate were compared between the two groups. Results: This study enrolled 197 patients, with 120 patients in group A and 77 patients in group B. There were no significant differences in age, gender, operation site, disease course, or preoperative ABG between groups A and B (p > 0.05). Both groups had significant postoperative improvement in hearing (group A: 30.98 ± 9.58 dB vs. 17.07 ± 9.92 dB, p < 0.001; group B: 29.75 ± 7.52 dB vs. 14.25 ± 9.07 dB, p < 0.001). The mean hearing gain in group A and group B was comparable (14.02 ± 11.91 dB vs. 15.50 ± 7.05 dB, p = 0.609). The wound healing rates of groups A and B were no differences (93.33% vs. 87.01%, p = 0.133). The patients in group B had a shorter operation duration (72.57 ± 11.32 min vs. 61.86 ± 9.27 min, p = 0.045) and less blood loss (12.38 ± 3.7 mL vs. 8.10 ± 2.43 mL, p = 0.004). Conclusions: Tragal perichondrium and COOK artificial material are reliable for functional and anatomical outcomes in endoscopic type 1 tympanoplasty, and COOK artificial material can save operation time and blood loss in surgery compared to the tragal perichondrium.